Management Scenarios Under Climate Change – A Study of the Nordic and Barents Seas - Hansen, Cecilie; Nash, Richard D. M.; Drinkwater, Kenneth F.; Hjøllo, Solfrid Sætre (Frontiers in Marine Science, 2019)
The effects of increasing fishing pressure in combination with temperature increase in the Nordic and Barents Seas have been evaluated using an end-to-end model for the area forced by a downscaled RCP 4.5 climate scenario. The scenarios that have been applied have used four different fractions of fisheries mortality at maximum sustainable yield (Fmsy); 0.6, 0.8, 1.0 and 1.1 x Fmsy. As it is highly likely that more ecosystem components will be harvested in the future, the four scenarios have been repeated with fishing on a larger number of ecosystem components, including harvesting of lower trophic levels (mesozooplankton and mesopelagic fish). The zooplankton biomass had an increasing trend, regardless of the increase in fishing pressure on their predators. However, when introducing harvest on the lower trophic levels, this increase was no longer evident. When harvesting more components, the negative response in biomass of pelagic and demersal fish to increasing harvest became more prominent, indicating an increasing vulnerability in the ecosystem structure to stressors. Although harvest on lower trophic level led to an immense increase in the total catch, it also resulted in a decrease in the total catches of pelagic and demersal fish, despite more species being harvested in these guilds.